2019
DOI: 10.1038/s41598-019-44336-7
|View full text |Cite
|
Sign up to set email alerts
|

Integrate CRISPR/Cas9 for protein expression of HLA-B*38:68Q via precise gene editing

Abstract: The determination of null- or low-expressed HLA alleles is clinically relevant in both hematopoietic stem cell transplantation and solid organ transplantation. We studied the expression level of a questionable (Q) HLA-B*38:68Q allele, which carries a 9-nucleotide (nt) deletion at codon 230–232 in exon 4 of HLA-B*38:01:01:01 using CRISPR/Cas9 gene editing technology. CRISPR/Cas9 gene editing of HLA-B*38:01:01:01 homozygous EBV B cell line resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Since HLA mismatches may produce severe graft –vs host disease (GvHD) and graft rejection, a misinterpretation of these variants could strongly affect transplant‐related mortality. Hence, several studies proposed assays and methods to discriminate between low expressed or non‐expressed HLA alleles, mainly based on EBV‐transformed cell lines or on recombinant HLA‐molecules' cloning and transfection in established cell lines, not easily reproducible in most laboratories. Gerritsen et al demonstrated that HLA‐A*23:19Q , which has a single polymorphism at position 619 (G > A) compared with HLA‐A*23:01:01 , has no expression by serology and flow cytometry, therefore, it should be reclassified as a null allele .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Since HLA mismatches may produce severe graft –vs host disease (GvHD) and graft rejection, a misinterpretation of these variants could strongly affect transplant‐related mortality. Hence, several studies proposed assays and methods to discriminate between low expressed or non‐expressed HLA alleles, mainly based on EBV‐transformed cell lines or on recombinant HLA‐molecules' cloning and transfection in established cell lines, not easily reproducible in most laboratories. Gerritsen et al demonstrated that HLA‐A*23:19Q , which has a single polymorphism at position 619 (G > A) compared with HLA‐A*23:01:01 , has no expression by serology and flow cytometry, therefore, it should be reclassified as a null allele .…”
Section: Discussionmentioning
confidence: 99%
“…Using the same approach, Foll et al reported the HLA‐A*32:11Q as a low expressed variant . More recently, Yin et al demonstrated that HLA‐B*38:68Q is a low expressing allele using the CRISPR/Cas9 gene‐editing technology …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations